(untitled) - Calder, Kent E. (Princeton, 1993)
Offering a reinterpretation of the relationship between Japanese business and the government, this study explores whether Japan's economic miracle was generated primarily by the Japanese state or by the nation's dynamic private sector.
Keywords: Industrial policy